Controlling basal plane sulfur vacancy in water splitting MoSx/NiF electrocatalysts through electric-field-assisted pulsed laser ablation - Chaudry Sajed Saraj; Subhash C. Singh; Roshan Ali; Abhishek Shukla; Gopal Verma; Ting Ting Zou; Weili Yu; Wei Li; Chunlei Guo (iScience, 2023)
Summary: Eco-friendly, efficient, and durable electrocatalysts from earth-abundant materials are crucial for water splitting through hydrogen and oxygen generation. However, available methods to fabricate electrocatalysts are either hazardous and time-consuming or require expensive equipment, hindering the large-scale, eco-friendly production of artificial fuels. Here, we present a rapid, single-step method for producing MoSx/NiF electrocatalysts with controlled sulfur-vacancies via electric-field-assisted pulsed laser ablation (EF-PLA) in liquid and in-situ deposition on nickel foam, enabling efficient water splitting. Electric-field parameters efficiently control S-vacancy active sites in electrocatalysts. Higher electric fields yield a MoSx/NiF electrocatalyst with a larger density of S-vacancy sites, suited for HER due to lower Gibbs free energy for H∗ adsorption, while lower electric fields produce an electrocatalyst with lower S-vacancy sites, better suited for OER, as shown by both experimental and theoretical results. The present work opens a horizon in designing high-efficiency catalysts, for a wide range of chemical reactions.